ЧИЗМАЧИЛИК ФАНИДАН ТАЛАБАЛАРНИНГ ФАННИ ЎЗЛАШТИРМАСЛИК САБАБЛАРИ ВА УНИНГ ОЛДИНИ ОЛИШ ОМИЛЛАРИ - Есбоғанова, Б.; Халимов, М. (FAN va JAMIYAT, 2018)
The given article deals with drawing subject, where we examine significant techniques in teaching subject and developing students‘ awareness about the subject, moreover,these issues help us to identify its place in society and infrostructure. In addition , there are given handouts designed on the basis of creative approach to develop drawing skills of learners.